Cryopreservation on Expression of Stemness-Genes in Mouse Fetal Liver Cells - Borysov, Petr A.; Dimitrov, Aleksey Yu.; Goltsev, Anatoliy N.; Ostankov, Maksim V. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):161.